2011
DOI: 10.1016/j.leukres.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the functional immunogenicity of chronic lymphocytic leukemia using epigenetic modifiers

Abstract: Chronic lymphocytic leukemia (CLL) is a malignancy arising from immune cells (B-lymphocytes) endowed with intrinsic antigen-presenting capabilities. Such a function however is lost during malignant transformation and CLL cells are well known for their inability to process and present antigens to the T-cell arm of the immune system. Instead, malignant CLL cells elicit a vast array of immune regulatory mechanisms conducive to T-cell dysfunction and immunosupression. Previously, we have shown that treatment of CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…A single manuscript has previously identified the epigenetic repolarization of human tumor infiltrating lymphocyte clones using 5A2, however the scope of this study lacked a detailed analysis of the mechanism and molecular phenotype [23]. In prior published studies we identified a number of demethylation-induced immunotherapeutic effects which in total lead to an increased antigen presenting phenotype in CLL cells, a result which complements our current findings [27]. …”
Section: Discussionsupporting
confidence: 79%
“…A single manuscript has previously identified the epigenetic repolarization of human tumor infiltrating lymphocyte clones using 5A2, however the scope of this study lacked a detailed analysis of the mechanism and molecular phenotype [23]. In prior published studies we identified a number of demethylation-induced immunotherapeutic effects which in total lead to an increased antigen presenting phenotype in CLL cells, a result which complements our current findings [27]. …”
Section: Discussionsupporting
confidence: 79%
“…Our group has also reported findings establishing a role for epigenetic modifiers in altering CLL biology. 7,8 Interestingly, various groups have reported elevated histone deacetylase (HDAC) expression in CLL B cells compared with HDAC expression in normal B cells and correlations of HDAC expression levels with prognostic factors. [9][10][11][12] Several studies have also begun to explore the therapeutic potential of HDAC inhibitors for CLL treatment.…”
Section: Introductionmentioning
confidence: 99%
“…39 In a later study, the epigenetic modifiers 5-aza-2-deoxycytidine and LAQ824 effectively restored immunogenicity in CLL cell lines and primary CLL patient cells. 40 The combination treatment simultaneously improved T-cell activation and APC function of CLL B cells.…”
Section: T-cell Functionmentioning
confidence: 98%